Assessment of Intellectual Profile of Pupils with Borderline Intellectual Functioning in Anambra State, Nigeria - Obibuba, Ijeoma M; Muoghalu, A. E. O. (Teaching, Learning, and Development, 2025)
Little is currently known about borderline intellectual functioning (BIF) in Nigeria, a condition characterized by an intelligence quotient between one and two standard deviations below the average that affects more than 14% of the population. Aims: The present study aimed to analyze the intellectual profile of school-aged pupils with BIF. Method and Procedure: The research employed the 'gold standard' in psychological assessments designed to measure differing intellectual capacities in pupils (WISC-IV) by administering to 204 pupils with BIF attending 20 sampled lower and upper primary schools in Onitsha Educational Zone, and their profile was compared with that of a control group of typically developing (TD) pupils. The results show that the WISC-IV profile of the pupils with BIF differed from that of the TD pupils, and the former’s performance was worse than the latter’s in all the measures considered. The pupils with BIF also showed significant differences between the four main factor indices, scoring lowest for working memory. At the same time, the TD control group’s profile was flat (as expected on the grounds of standardization criteria). No differences were found between the profiles of pupils with and without a comorbid neurodevelopmental disorder. The study findings support the hypothesis that individuals with BIF have a characteristic profile with specific weaknesses. Following the study's findings, this research recommends that the government should embark on modalities that will enhance environmental adjustments for developing children, treatment of comorbid conditions, and early interventions.